A Randomized Fellow-Eye Clinical Trial to Evaluate Patient Preference for Dexamethasone Intracanalicular Insert or Topical Prednisolone Acetate for Control of Postoperative Symptoms Following Bilateral Femtosecond Laser in Site Keratomileusis (LASIK) - Greenwood MD (Dove Medical Press, 2020)
Michael D Greenwood,1 Richard A Gorham,2 Keeley R Boever2,3 1Vance Thompson Vision, West Fargo, ND, USA; 2Ektropia Solutions LLC, Laguna Beach, CA, USA; 3Vance Thompson Vision, Sioux Falls, SD, USACorrespondence: Michael D GreenwoodVance Thompson Vision, 505 32nd Ave E, Suite B, West Fargo, ND 58078, USATel +1 701-566-5390Fax +1 701-639-7199Email Michael.Greenwood@VanceThompsonVision.comPurpose: To determine the preference of patients undergoing bilateral LASIK for either the dexamethasone intracanalicular insert or topical prednisolone acetate for control of postoperative symptoms and ocular surface signs.Methods: In this randomized clinical trial, one eye was randomized to receive the dexamethasone insert or topical prednisolone acetate 1% four times daily for one week and 2 times daily for a second week; the fellow eye received the alternate therapy. One month postoperatively, patient preference for these two therapies was assessed using an adapted COMTOL questionnaire. Ocular comfort was assessed using the SPEED questionnaire. Corneal staining and uncorrected distance visual acuity (UDVA) were also assessed.Results: Twenty patients participated. At Month 1, 80% of patients preferred the dexamethasone insert, 10% preferred prednisolone acetate, and 10% expressed no preference (p< 0.001). SPEED scores measuring ocular comfort/discomfort related to dry eye symptoms were similar between groups (p=0.72), and both the incidence of patient-reported ocular dryness and the corneal staining scores were similar between groups. Both groups attained the same final UDVA.Conclusion: Patients undergoing elective bilateral femtosecond LASIK surgery overwhelmingly (by an 8-to-1 margin) preferred the dexamethasone insert to topical prednisolone acetate for postoperative treatment. The insert produced comparable ocular comfort, corneal staining, and visual acuity outcomes to topical prednisolone. The insert is an appropriate means of postoperative symptom control in this quality of life-conscious population.Keywords: dexamethasone, Dextenza, LASIK, randomized trial, patient preference, ocular surface symptoms